Screening of cytodex 3 microcarrier in microwell attachment plates for mammalian cells - 640170 Nurul Hidayah Khairuddini, 1995- (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Sains (Biologi - Industri)) - Universiti Teknologi Malaysia, 2018